FEMALE MASCULINITY IN THE NOVEL THE SPY BY PAULO COELHO: A REVIEW ON THE MAIN CHARACTER - Dewi Rahayu; Ni Made Widisanti S; Tetty Yukesti (Journal Albion : Journal of English Literature, Language, and Culture, 2019)
ABSTRACTThis study aims at denoting  the image of female masculinity through the study of the main character in the novel The Spy by Paulo Coelho. The main character, Mata Hari,  works as a dancer and hetaira, but is accused of spying because of her profession. The method used in this research is descriptive qualitative with library research technique. The results of this study indicate that female masculinity described in the main character is considered hegemonic masculinity, that is, the kind of  masculinity formed through behavior, personal experience, and cultural processes. This masculinity is denoted in the presence of the main characters characteristics, such as  self-nature, adventurous, free, selfish, reckless, active, and courageous.Keyword : Female masculinity, Hetaira, Masculinity-femininity.